BIO-NANOTECHNOLOGY-BASED SOLUTIONS FOR SUSTAINABLE WASTE MANAGEMENT AND POLLUTION - KAMAL , UB; SHARMIN , S; RIZWAN , M; CHOUDHARY , ZA; LATIF , N; SHAMAS , A; ALI , A (Biological and Clinical Sciences Research Journal, 2024)
Waste management and pollution reduction are critical global challenges that demand innovative and sustainable solutions. Traditional methods often fall short in terms of efficiency and environmental impact. Biological nanotechnology, particularly the use of biosurfactants and nanoenzymes, offers promising alternatives for addressing environmental pollutants such as hydrocarbons, textile dyes, and heavy metals. Objective: This study aimed to evaluate the effectiveness of bio-nanotechnology-based solutions, specifically biosurfactants and nanoenzymes, in waste management and pollution reduction, focusing on sustainability and environmental impact. Methods: A quantitative research approach was employed to assess the efficacy of bio-nanotechnology in waste treatment and pollution reduction. Laboratory experiments were conducted to explore the degradation capacity of biosurfactants and nanoenzymes on various pollutants. The study also involved a survey of 167 industry professionals to evaluate the potential of bio-nanotechnology in enhancing waste treatment efficiency and environmental sustainability. Data on pollutant elimination efficacy, degradation rates, soil health, metal contaminant levels, and CO2 emissions were collected. Statistical analysis was performed to compare the outcomes of nano-bioremediation with traditional methods. Results: The laboratory experiments demonstrated a high treatment capacity, with pollutant elimination efficacy exceeding 86% and degradation rates significantly faster than conventional treatments. The survey results indicated that bio-nanotechnology could enhance waste treatment efficiency and environmental friendliness by 20-40%. Nano-bioremediation led to a 23% improvement in soil health, a 32% reduction in metal contaminants, and a 14-19% decrease in CO2 emissions from waste processing compared to conventional methods. Conclusion: The study’s findings suggest that bio-nanotechnology presents a novel, sustainable solution for waste management and pollution reduction. The significant improvements in pollutant elimination, soil health, and reduction of metal contaminants and CO2 emissions highlight the potential of this approach to address global environmental challenges more effectively than traditional methods. Further research and development are recommended to optimize and scale up these technologies for broader application.